Demographic-governance factors shaping cryptocurrency holding behavior - Dang THN; Balli F; Balli HO; Kilic I (Elsevier B.V., 2025)
Employing cross-sectional data of 142 countries worldwide, this paper examines the macroeconomic factors in shaping cryptocurrency adoption. We find that the aggregate impact of inflation volatility on crypto adoption is dependent on the level of corruption control in higher-income countries. The control of corruption appears to discourage cryptocurrency adoption, emphasizing the role of institutional trust in financial choices. We also find that higher emigrant ratios in non-high-income and lower-income countries are associated with increased cryptocurrency usage, which suggests that migrants tend to use cryptocurrencies for faster, cheaper remittances compared to traditional services. Last, we find that internet penetration plays a key role in crypto adoption, particularly in higher-income countries with advanced digital infrastructure.
Keywords: Cryptocurrency adoption; Crypto ownership; Inflation volatility; Control of corruption; Emigrants; internet penetration; Institutional trust; Digital finance